Integrasi Nilai-Nilai Moderasi pada Pendidikan Anak Usia Dini Berbasis Living Values Education (LVE) - Khoirul Mudawinun (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The last few years a distinct religious color in Indonesian society is facing a great shock with the presence of religious radicalism phenomenon that has been occurring in recent years. It becomes a major task of educational institutions, especially Early Education which is the basis of a strong ideological understanding to choose the right formulation as a prefect and curative action. This paper seeks to initiate integrated education with moderate values ​​in Early Child-based Living Values ​​Education (LVE) with Research and development (R & D) Methods. The results revealed: (1) Basic Competence in Early Childhood Education at Permendikbud 146 Year 2014 integrated with Moderation Values. (2) Process of internalization of moderation values through phase; Knowing the good, feelling the good, and doing the good. The form of moderation learning based on Living Values Education (LVE) as follows: (a) Determining the learning objectives, (b) Determining the target values ​​to be built, (c) Using the integrated approach ) Using comprehensive methods, and (e) Determining learning strategies.